AN ANALYSIS OF INVESTING HABITS AMONG WORKING WOMEN - Irshad Ahmad Reshi; Dr.T.Sudha (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
A nation's saving rate and investment rate form a positive feedback loop that leads to increased capital formation. Indian families are the most financially secure in the world because they save more than anyone else. A woman's salary was secondary to the breadwinner's income in those days. However, a woman's earnings have gained prominence in the modern world. Women's savings are crucial for helping their families weather the inevitable storms of life. Investing styles of men and women have been found to differ in numerous studies. Women's lower risk tolerance leads to lower investment returns. The purpose of this paper is to analyse the investment habits of financially savvy women. Researched goods include gold, mutual funds, loans, preferred stock, stock, investment trusts, policies, and cash accounts, among others. In addition, the study has attempted to identify the most influential elements in the decision-making process of investors. According to the study's findings, the investment risk associated with banks is exceptionally low, while that associated with the post office and mutual funds is relatively high.